Interactions Between Rumen Microbes, VFAs, and Host Genes Regulate Nutrient Absorption and Epithelial Barrier Function During Cold Season Nutritional Stress in Tibetan Sheep - Liu, Xiu; Sha, Yuzhu; Dingkao, Renqing; Zhang, Wei; Lv, Weibing; Wei, Hong; Shi, Hao; Hu, Jiang; Wang, Jiqing; Li, Shaobin; Hao, Zhiyun; Luo, Yuzhu (Frontiers in Microbiology, 2020)
As one of the important ruminants of the Qinghai-Tibet Plateau, Tibetan sheep are able to reproduce and maintain their population in this harsh environment of extreme cold and low oxygen. However, the adaptive mechanism of Tibetan sheep when nutrients are scarce in the cold season of the Plateau environment is unclear. We conducted comparative analysis rumen fermentation parameters, rumen microbes, and expression of host genes related to nutrient absorption and rumen epithelial barrier function in cold and warm season Tibetan sheep. We found that concentrations of the volatile fatty acids (VFAs) acetate, propionate and butyrate of Tibetan sheep in the cold season were significantly higher than in the warm season (P<0.05). Microbial 16S rRNA gene analysis revealed significant differences in rumen microbiota between the cold and warm seasons, and the abundance of microbial in the cold season was significantly higher than that in the warm season (P<0.05), and the lack of nutrients in the cold season led to a significant reduction in the expression of SGLT1, Claudin-4, and ZO-1 genes in the rumen epithelium. Correlation analysis revealed significant associations of some rumen microorganisms with the fermentation product acetate and the rumen epithelial genes SGLT1, Claudin-4, and ZO-1.